(Un)Sustainability and Organization Studies: Towards a Radical Engagement - Ergene, Seray; Banerjee, Subhabrata Bobby; Hoffman, Andrew J. (Organization studies, 2021)
In this essay, we trace the evolution of the field of sustainability in management and organization studies and narrate its epistemological twists and turns. Concerned by the current trajectory that tends to diminish a focus on political concerns, we propose a new research agenda, an ecological case for business, that transforms our paradigmatic orientation in four shifts: (1) altering our epistemological lenses from managerial to critical perspectives; (2) altering our ontological lenses from realist to relational view; (3) changing the way we design and conduct research from discipline-focused to interdisciplinary knowledge; and (4) transforming our scholarly stance from value-neutral to engaged scholarship. We argue that these shifts have capacities to overcome the conceptual limitations of the business case and, more fundamentally, help us question our scholarly positioning to the ongoing socio-ecological crises.